Sosialisasi Media Pembelajaran dan Program Statistika di SD Negeri Setu 01 Cipayung - Ek Ajeng Rahmi Pinahayu; Iim Marfu’ah (Jurnal PkM Pengabdian kepada Masyarakat, 2020)
The teaching and learning process is essentially a communication process, which is the process of delivering messages from the message source through certain channels / media to the recipient of the message. In teaching and learning activities, the media is one of the factors that determine the success of the learning process. Teaching media such as snakes and ladders, domino cards and monopoly games can enhance the learning process of students in teaching, which in turn is expected to enhance the learning outcomes achieved. In PTK (Classroom Action Research) conducted by teachers, teachers can develop in terms of the use and use of learning media to improve the quality of learning in the classroom. Training in the use of instructional media and training in research data processing statistics programs to develop the quality of CAR carried out by teachers in schools is useful for improving the skills of elementary school teachers in using software SPSS in processing Classroom Action Research (PTK) data.